Under the Veil Feminism and Spirituality in Post-Reformation England and Europe. - Quinsey, Katherine M. (Newcastle upon Tyne : Cambridge Scholars Pub., 2012)
For women in early modern Europe, the Reformation and the Enlightenment entailed both new freedom and new restrictions. In response to an ideology that immured the female mind and spirit inside the body, women found in religion a hope for individual freedom, a sense of self-identity, and a justification for gender equality. Under the Veil: Feminism and Spirituality in Post-Reformation Europe invokes the veil's dual significance, as the marker of the religious woman, and as the metaphoric veil ...
TABLE OF CONTENTS; INTRODUCTION; JULIE HIRST; SYLVIA BROWN; ANN M. LITTLE; MARIE COMISSO; KATHERINE M. QUINSEY; HUMBERTO GARCIA; MITA CHOUDHURY; PEGGY SCHALLER; ALICIA L. KERFOOT; CONTRIBUTORS; INDEX.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Feminism -- History; Feminism -- Religious aspects; Women and religion -- History; Feminism -- History; Feminism -- Religious aspects; Women and religion -- History; RELIGION / Religious Intolerance, Persecution & Conflict; Electronic books